1995
DOI: 10.1063/1.871284
|View full text |Cite
|
Sign up to set email alerts
|

Detached scrape-off layer tokamak plasmas

Abstract: The equilibrium and stability of scrape-off layer plasmas are considered using a 1-dimensional treatment of coupled heat conduction and pressure balance equations. It is found that, for sufficiently low temperature and high neutral density, a region of greatly reduced power flux to the end plate can be achieved. The plasma in the vicinity of the end wall is characterized by a sharp plasma pressure gradient and a relatively low temperature, 1 < To < 10 eV. PACS 52.40.Hf, 52.55.Fa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Firstly, with two measurements of the plasma temperature on a given field line and an estimate of the heat flux to the divertor plate, the two constants of integration and the volumetric heat source required for a solution of the conduction equation can be evaluated. The interpolated field line calculation has been carried out with Alcator C-Mod data, including radiation losses, by LaBombard et al [20], and including both radiation loss and momentum loss due to collisions with neutrals by Kesner [38]. In both cases, it has been found that the temperature drops only at a very short distance from the target (poloidally and along a field line), giving a detachment Lfront' parallel to the plate.…”
Section: Neutral Particle Flux Modelmentioning
confidence: 99%
“…Firstly, with two measurements of the plasma temperature on a given field line and an estimate of the heat flux to the divertor plate, the two constants of integration and the volumetric heat source required for a solution of the conduction equation can be evaluated. The interpolated field line calculation has been carried out with Alcator C-Mod data, including radiation losses, by LaBombard et al [20], and including both radiation loss and momentum loss due to collisions with neutrals by Kesner [38]. In both cases, it has been found that the temperature drops only at a very short distance from the target (poloidally and along a field line), giving a detachment Lfront' parallel to the plate.…”
Section: Neutral Particle Flux Modelmentioning
confidence: 99%
“…One operational regime that maximizes the influence of neutral particle collisions is that of the detached plasma regime. [3][4][5][6][7] A detached plasma is characterized in part by formation of a cool dense neutral layer in front of a material surface. Conditions are such that T e ϳ1→5 eV and the plasma density is ϳ10 20 →10 21 m Ϫ3 ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…All dimensions are in metres. [8,12]. This model is based on the two-point model [13,14], but has terms to account for momentum transfer from the ions to neutral atoms in the divertor and a term to account for the power lost by radiation.…”
Section: Neutral Density Measurementsmentioning
confidence: 99%